Min al-imtiyāz al-ijtimā'ī ila al-tasāmuḥ al-dīnī: Ṣūrat li ta'āyush mujtama' Minangkabau al-Muslim wa mujtama' Nias al-Masīḥī - Ashadi, Andri; Sefriyono, Sefriyono (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2023)
This article challenges the claims that assert that Indonesian Muslims are fundamentally conservative, if not fundamentalist, in nature. The discussion is grounded in a case study of peaceful coexistence between the Muslim Minang Community (KMM) and the Christian Nias Community (KKN) over several centuries in Padang Pariaman. To obtain this perspective, this study centres on evidence from customary land agreements between the two communities, reinforced by observations and interviews with traditional and religious figures from both communities between 2017 and 2018. Among the most significant findings is that KMM has developed a concept of land management rights (ulayat nagari) that differs from state-controlled management. The management of ulayat nagari land not only places emphasis on economic access but also opens up various social and even religious concessions. Through the concessions of 1927 and 1928, KKN gained rights to the ownership of ulayat nagari land, recognition of their village head (penghulu), and adherence to the customs of KKN. Furthermore, two KKN churches stand on this ulayat nagari land as symbols of religious freedom.